Predicting Individual Preferences in Mindfulness Techniques Using Personality Traits - Tang, Rongxiang; Braver, Todd S. (Frontiers in Psychology, 2020)
The growing popularity of mindfulness-based interventions has prompted exciting scientific research regarding their beneficial effects on well-being and health. Most mindfulness programs are provided as multi-faceted packages encompassing a set of different mindfulness techniques, each with distinct focus and mechanisms. However, this approach overlooks potential individual differences which may arise in response to practicing various mindfulness techniques. The present study investigated preferences for four prototypical mindfulness techniques (focused attention, open monitoring, loving-kindness, and body scan) and identified factors that may contribute to individual differences in these preferences. Participants without prior mindfulness experiences were exposed to each technique through audio-guided instructions and were asked to rank their preferences at the end of all practices. Results indicated that preferences for loving-kindness were predicted by empathy, and that females tended to prefer loving-kindness more than males. Conversely, preferences for open monitoring were predicted by nonreactivity and nonjudgment of present moment experiences. Additionally, higher state mindfulness was detected for individuals’ preferred technique relative to other alternatives. These findings suggest that individuals tend to prefer techniques compatible with their personalities, as the predictor variables encompass trait capacities specifically relevant to practicing these techniques. Together, our results suggest the possibility that assessing individual difference and then tailoring mindfulness-based interventions to individual needs could be a useful way to improve intervention effectiveness and subsequent outcomes.